Some Fixed Point Results by Altering Distances between Points - Jha, K; Pant, RP; Thapa, P (Kathmandu University Journal of Science Engineering and Technology, 2010)
The theory of fixed point is a very extensive field, which has various applications. This paper is the survey work on some fixed point theorems by altering distances between points in metric space.